The Verdict: Proton Pump Inhibitors have been found guilty of causing death. Any objections? - Ünal, Hakan Ümit; Saruç, Murat (Turkish Journal of Gastroenterology, 2017)
Abstract Cite this article as: Ünal HÜ, Saruç M. The Verdict: Proton Pump Inhibitors have been found guilty of causing death. Any objection? Turk J Gastroenterol 2017; 28: 544-5.